The Word is Not the Sting, Or Is It? - Johnston, Paul Dennithorne (ETC: A Review of General Semantics)
Profiles dictator M. E. O'Wally, chief executive officer of the Earth and Environs. Powerful weapon used by O'Wally to dominate others; Important factor in O'Wally's rise to power; Shameful secret of O'Wally.